Early age porosity and pore size distribution of cement paste with flue gas desulphurisation (FGD) waste - Khatib, Jamal M.; Mangat, Pritpal S.; Wright, Lee (Journal of Civil Engineering and Management, 2013)
This paper is part of a wide-ranging investigation on the use of flue gas desulphurisation (FGD) waste in cement-based materials. It reports the results on the porosity and pore size distribution of cement paste containing varying amounts of simulated FGD waste. The water to binder ratio was 0.5. The binder consists of cement and simulated FGD. The FGD is a combination of fly ash and gypsum ranging from 0% to 100%. Cement in the pastes was partially replaced with 25% FGD (by weight). The porosity and pore size distribution of cement pastes was determined during the early stage of hydration. Increasing the amount of gypsum does not increase the pore volume. However, increasing the amount of gypsum in the paste leads to an increase in the threshold diameter and a decrease in the percentage of small pores in the paste, both indicating a coarser pore structure. The results of this investigation were compared with data at longer curing periods.